1998
DOI: 10.1172/jci650
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin alters superoxide and nitric oxide release in prehypertensive rats.

Abstract: Constitutive nitric oxide synthase (cNOS) with insufficient cofactor (6R)-5,6,7,8-tetrahydrobiopterin (H4B) may generate damaging superoxide (O2-). This study was designed to determine whether cNOS-dependent generation of O2- occurs in spontaneously hypertensive rats (SHR) before the onset of hypertension. Aortas from 4-wk-old SHR and Wistar-Kyoto rats were used. cNOS was stimulated by calcium ionophore A23187. In situ measurements of nitric oxide and hydrogen peroxide by electrochemical sensors and O2- produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
209
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(222 citation statements)
references
References 40 publications
9
209
2
2
Order By: Relevance
“…Aortae of spontaneously hypertensive rats had higher production of superoxide and reduced release of NO compared with normotensive rats, an effect that was blunted in the presence of exogenous BH 4 . 19,24 Our present study confirms these experimental observations in human subjects with essential hypertension in whom oral BH 4 reduced BP, likely by reversing the uncoupling of NO synthase and improving NO bioavailability. A previous study by Higashi et al 25 showed that parenteral infusion of BH 4 improved endothelial function in hypertensive patients, but this is the first study demonstrating the effects of oral BH 4 on endothelial function and BP.…”
Section: Potential Mechanismssupporting
confidence: 86%
“…Aortae of spontaneously hypertensive rats had higher production of superoxide and reduced release of NO compared with normotensive rats, an effect that was blunted in the presence of exogenous BH 4 . 19,24 Our present study confirms these experimental observations in human subjects with essential hypertension in whom oral BH 4 reduced BP, likely by reversing the uncoupling of NO synthase and improving NO bioavailability. A previous study by Higashi et al 25 showed that parenteral infusion of BH 4 improved endothelial function in hypertensive patients, but this is the first study demonstrating the effects of oral BH 4 on endothelial function and BP.…”
Section: Potential Mechanismssupporting
confidence: 86%
“…The stimulatory GTPCHI⅐GFRP complex consists of three layers, (GFRP) 5 -(GTPCHI) 10 -(GFRP) 5 , with overall dimensions of Ϸ130-Å height and 93-Å diameter ( Fig. 2 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic defects affecting GTPCHI activity cause hyperphenylalaninemia and severe neurological disorders such as 3,4-dihydroxyphenylalanine-responsive dystonia (1)(2)(3)(4). The BH 4 deficiency that occurs because of abnormalities in the control mechanisms of GTPCHI have been found in a variety of diseases ranging from vascular diseases such as diabetes, hypertension, and atherosclerosis (5)(6)(7)(8) to neurological diseases such as Parkinson's and Alzheimer's (9,10). Recent findings that guanine and 8-hydroxyguanine inhibit GTPCHI activity in a GTPCHI feedback regulatory protein (GFRP)-dependent manner raise the possibility that a BH 4 deficiency occurs in LeschNyhan syndrome and Parkinson's disease (11).…”
mentioning
confidence: 99%
“…NOS enzymes have tetrahydrobiopterin as a cofactor that mediates coupling of oxygen reduction to haem catalysed L-arginine oxidation to form NO and citrulline. In recent years in has become apparent that when NOS enzymes lack substrate (arginine), cofactor (tetrahydrobiopterin) or specific protein-protein interactions (Xia et al 1996;Cosentino et al 1998;Bender et al 1999;Pou et al 1999;Song et al 2002;Ou et al 2003), the oxygen reduction and arginine oxidation become 'uncoupled' leading to generation of superoxide by the enzymes. In endothelial cells this uncoupling leads to superoxide-mediated endothelial dysfunction (Cosentino & Lü scher 1999;Cosentino et al 2001).…”
Section: Nos Enzymes Are a Potential Source Of Both No And Superoxidementioning
confidence: 99%